2020
DOI: 10.1002/admi.202001588
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus‐Containing C12H27O4P as Functional Electrolyte Additives for High‐Voltage LiNi0.5Mn1.5O4/Graphite Li‐Ion Batteries with Excellent Electrochemical Performance

Abstract: As the most promising cathode material in new energy resources, LiNi0.5Mn1.5O4 (LNMO) are widely researched due to its high platform, low cost, and environment‐friendliness, when they are assembled with graphite into battery which can lead to a faster capacity decay because of unstable solid–liquid interface. This work is devoted to stabilize electrolyte and protect interface of LNMO/graphite full battery by adding multifunctional additive, tributyl phosphate (TBP). Theory calculation which exhibits disconnect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…The TBP molecule consists of a single polar PO group and three hydrophobic butyl chains connected by ester bonds. 18 As shown in Fig. 1a, density functional theory (DFT) calculation demonstrates that the O atom in the PO group has more negative surface electrostatic potential (ESP) than the O atom in H 2 O, indicating stronger interaction between TBP and Zn 2+ .…”
Section: Resultsmentioning
confidence: 97%
“…The TBP molecule consists of a single polar PO group and three hydrophobic butyl chains connected by ester bonds. 18 As shown in Fig. 1a, density functional theory (DFT) calculation demonstrates that the O atom in the PO group has more negative surface electrostatic potential (ESP) than the O atom in H 2 O, indicating stronger interaction between TBP and Zn 2+ .…”
Section: Resultsmentioning
confidence: 97%
“…This shows that the deposit on the cathode is much less than that on the anode, which is consistent with the results in the literature. 18 Even so, at a higher magnification, it is still found that there is deposit on LNMO particles of the cycled TAP-free cell (Figure 2b (cathode)), while the surface of LNMO particles of the cycled cell with 1.0 wt % TAP is still clean (Figure 2d (cathode)).…”
Section: Influence Of Tap Additive On Lnmo/graphitementioning
confidence: 92%
“…A similar result has been observed in another work. 18 These deposits are believed to be caused by reduction of electrolyte and electrolyte oxidation products. However, the deposit on the surface of graphite anode from the cycled cell with 1 wt % TAP is much less (Figure 2c (anode)), and the surface of graphite particles is smooth and clean (Figure 2d (anode)).…”
Section: Influence Of Tap Additive On Lnmo/graphitementioning
confidence: 99%
See 1 more Smart Citation
“…the electrochemical and electrochromic properties. The lithium ion (Li + )-based electrolytes have a vast array of applications, including electrochromic devices (ECDs), [1][2][3] batteries, [4] capacitors, [5] and so on. It is evident that the lithium-ion trapping in the host structure would result in an electrode degradation by direct or indirect electrochemical redox in electroactive support electrolytes, giving rise to irreversible electrochemical reactions.…”
mentioning
confidence: 99%